Rash Model Approach for Analysis of Misconception on Chemistry Learning with Distractor Analysis - Sri Mulyani; Nur Haniza; Dimas Gilang Ramadhani; Lina Mahardiani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Multiple-choice questions can be used to identify misconceptions through distractor analysis. Distractor analysis for identifying misconceptions using Rasch modelling to find out how students choose options and whether they have any misconceptions. The test instrument uses questions from the teacher association in Indonesia to assess students’ ability to master chemical contexts. The number of question items used is 35 and has been validated and tested for reliability to be feasible to use. Questions were given to 462 first-year high school students. The fit item analysis results show that there are several questions related to clothing that indicate misconceptions. This is supported by the distractor analysis value, which found that misconceptions indicate questions related to electrolysis, the incidence of colligative properties in daily life and the factors that affect corrosion. The distractor’s value and the option probability curve are used to see how students know the ideas offered. The analysis results found that the material in the form of concepts and their application showed a large misconception, in which students would find it difficult to combine concepts and their applications.